Service Quality of Private Higher Educational Institutions in Kabankalan City as a Determinant of Student Retention - Albayda, Margaret Rose (Journal of Interdisciplinary Perspectives, 2025)
Research on service quality in higher education has rarely focused on component cities, such as Kabankalan, in Negros Occidental. Although strategically situated as a business and trade hub in the Negros Island Region, Kabankalan ranks low in school service capacity, with only 2.53 percent of higher education students in the province enrolled in the private higher educational institutions (HEIs) in the city. This study assessed service quality as a determinant of student retention in private HEIs in Kabankalan using the SERVQUAL model, which includes tangibility, reliability, responsiveness, assurance, and empathy. A total of 361 first- and second-year students from three private HEIs were surveyed through convenience sampling. The findings revealed that overall service quality has a significant impact on student retention (p < .001). Among the dimensions, only empathy and tangibility were significant determinants (p < .001). Interestingly, although responsiveness received the highest expectation (M = 6.27) and perception scores (M = 6.18), it had no significant impact on retention (p = .781). The study recommends implementing quality management systems focused on student-centered communication, emotional support, and facility upgrades to address service gaps in empathy and tangibility. This research serves as a baseline for further studies on the long-term effects of service quality in private HEIs within component cities like Kabankalan.